2022
DOI: 10.21733/ibad.1039215
|View full text |Cite
|
Sign up to set email alerts
|

Afetlerde Kadın ve Toplumsal Cinsiyet Perspektifi ile Çıkarılması Gereken Dersler (Haiti ve Japonya Depremi Örneği)

Abstract: 1-Makalede etik kurulu izni ve/veya yasal/özel izin alınmasını gerektiren bir durum yoktur. 2-Bu makalede araştırma ve yayın etiğine uyulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…As a result of global climate change, drought in the basin is expected to increase even more in the future. In line with this expectation, it is important to identify risks and hazards, take all necessary precautions, take responsibility for disasters and to raise awareness in order to prevent and reduce damages within the scope of the modern disaster management approach [63]. In line with the disaster management approach, for the drought disaster and other possible disasters in the basin:…”
Section: Discussionmentioning
confidence: 99%
“…As a result of global climate change, drought in the basin is expected to increase even more in the future. In line with this expectation, it is important to identify risks and hazards, take all necessary precautions, take responsibility for disasters and to raise awareness in order to prevent and reduce damages within the scope of the modern disaster management approach [63]. In line with the disaster management approach, for the drought disaster and other possible disasters in the basin:…”
Section: Discussionmentioning
confidence: 99%
“…An earthquake can not only shake the physical foundations but also damage women's roles in the family and society. It affects gender equality, sexual and reproductive health rights, and increases poverty and ongoing challenges related to violence (Enarson, 2012;Gündüz, 2022). Campbell et al (2016) reported that women who survived the earthquake in Haiti experienced various physical and psychological problems and also experienced different forms of violence from their husbands or boyfriends.…”
Section: Discussionmentioning
confidence: 99%